Energy performance evaluation of a photovoltaic window - Serrano-Casares, Francisco Víctor; Navas Frías, Verónica (My University, 2018)
A photovoltaic window specially built by a manufacturer has been studied. An amorphous silicon photovoltaic module encapsulated between two transparent glass sheets, an air chamber and a second double glass sheet with an air chamber forms the photovoltaic window. Everything is framed in a PVC structure. The effective dimensions of the a-Si photovoltaic module are 0.57x1.17 m2, equivalent to a standard measurement of 0.60x1.20 m2. To know the electrical characteristics of PV window in standard test conditions, a test in accordance with IEC standard 61646 it has carried out. A peak power of 50.74 Wp was obtained. Measurements of energy production in real sunlight were carried out. The window was placed vertically facing south on a test bench. Measurements of the energy produced by the photovoltaic window were made in several sunny days of August and September 2016 from sunrise to sunset. On average, the irradiance received on the plane of the photovoltaic window was 4114 Wh/m2 and the energy produced 71.2 Wh each day. These results match those obtained using the Malaga radiation databases. For one square meter of the window studied, 79.868 kWh/m2/year are obtained, when an overall efficiency of 0.8 is considered. Integrating this PV window in a building in Malaga (Spain), an annual electric production of 345030 kWh is obtained when a glazing surface of 4320 m2 is considered. This energy is enough to meet the annual electricity needs of the 68 household of the building.
Keywords: Energía fotovoltaica; PV window; A-Si; Building integrated PV (BIPV)